Age-related cerebral ventriculomegaly occurs in patients with primary ciliary dyskinesia - Franziska Eisenhuth; Joy E. Agbonze; Adam M. R. Groh; Jesse M. Klostranec; David A. Rudko; Jo Anne Stratton; Adam J. Shapiro (Fluids and Barriers of the CNS)
Abstract Primary ciliary dyskinesia (PCD) is a genetic disorder causing motile ciliary dysfunction primarily affecting the respiratory and reproductive systems. However, the impact of PCD on the central nervous system remains poorly understood. Rodent models of PCD exhibit marked hydrocephalus leading to early animal mortality, however, most humans with PCD do not develop hydrocephalus for unknown reasons. We hypothesized that patients with PCD exhibit sub-clinical ventriculomegaly related to ependymal motile ciliary dysfunction. We demonstrated highly specific expression levels of known PCD-related genes in human brain multiciliated ependymal cells (p < 0.0001). To assess ventricular size, computed tomography sinus images from patients with PCD (n = 33) and age/sex-matched controls (n = 64) were analysed. Patients with PCD displayed significantly larger ventricular areas (p < 0.0001) and Evans index (p < 0.01), indicating ventriculomegaly that was consistent across all genetic subgroups. Ventricular enlargement correlated positively with increasing age in patients with PCD compared to controls (p < 0.001). Additionally, chart review demonstrated a high prevalence (39%) of neuropsychiatric/neurological disorders in adult PCD patients that did not correlate with degree of ventriculomegaly. Our findings suggest that patients with PCD may have unrecognized, mild ventriculomegaly which correlates with ageing, potentially attributable to ependymal ciliary dysfunction. Further study is required to determine causality, and whether ventricular enlargement contributes to neuropsychiatric/neurological or other morbidity in PCD.